Comparative analysis of microbial diversity in various kombucha starter cultures in Malaysia using the random amplified polymorphic DNA (RAPD) approach - Augustine, Nur Syafiqah Syahmimie; Chong, Eric Tzyy Jiann; Wong, Clemente Michael Vui Ling; Nasir, Nurul Farhana (University of Malaya, 2025)
Kombucha is sweetened black tea fermented with symbiotic culture of bacteria and yeasts (SCOBY) and has been widely consumed for its purported health benefits. The microbial consortium in kombucha is dominated by yeasts such as Brettanomyces sp. and Zygosaccharomyces sp., as well as acetic acid bacteria (AAB), Komagataeibacter sp. and Acetobacter sp. However, the source of SCOBY and substrates used may affect the microbial diversity as well as the biochemical, and flavour of the kombucha. Identifying the microbial population is important as the use of undefined starter cultures may lead to variable metabolite production and increase the risk of food pathogen contamination which can pose harm to human health. This study aims to isolate the microbes from kombucha in Malaysia for the future development of a new starter culture with specific species for the safe consumption of kombucha. Briefly, a total of 100 colonies were isolated from nine kombucha starter cultures with selective culture plates. Differences in colony morphology were observed based on their colours, surface texture, elevation, and margin. Their phenotypic morphology and genetic diversity were screened using microscopic examination, coupled with a catalase test and random amplified polymorphic DNA (RAPD), respectively. Based on the data, 51% of the isolates showed yeasts morphology under microscopic examination, while the rest were bacteria. Additionally, 55.79% of the isolates showed distinct banding profile patterns in the RAPD assessments. In conclusion, the data of this study shows that there is a diverse microbial consortium in different starter cultures of kombucha from Malaysia, mainly predominated by Gram-negative AAB and Gram-positive yeasts. Identification at the species level is to be conducted in the future. By understanding the microbiota diversity in kombucha, it contributes to the development and production of a safe functional drink.